2006
DOI: 10.1188/06.onf.614-624
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Physical Activity in Patients Undergoing Hematopoietic Stem Cell Transplant

Abstract: Patients undergoing HSCT require considerable supportive nursing care immediately following transplant. Clinicians and researchers need to strive for effective symptom management to improve the likelihood of successful outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 38 publications
5
104
0
13
Order By: Relevance
“…Our result is consistent with findings from other studies that measure sleep disturbances at least one time during inpatient treatment. [6][7][8][9] In line with our outcome, Hacker and Ferrans 8 showed that sleep difficulties are significantly worse during hospital stay compared with time points before admission and two weeks after discharge. At six weeks after discharge sleep problems were a little less pronounced than before admission.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our result is consistent with findings from other studies that measure sleep disturbances at least one time during inpatient treatment. [6][7][8][9] In line with our outcome, Hacker and Ferrans 8 showed that sleep difficulties are significantly worse during hospital stay compared with time points before admission and two weeks after discharge. At six weeks after discharge sleep problems were a little less pronounced than before admission.…”
Section: Discussionsupporting
confidence: 70%
“…In sum, the results of these studies show that disturbed sleep is one of the most prominent concerns among patients; sleep difficulties occur frequently and are worst during the inpatient treatment. [6][7][8][9][10][11] Anderson et al 6 assessed the symptom burden in 100 patients undergoing autologous SCT during their hospital stay. They identified sleep disturbance as one of the most pronounced symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…This therapy, which was used in the last two decades for high-risk acute lymphoblastic leukemia (ALL) (typically at 18 Gy dose), is strongly associated with physical inactivity during adulthood. 9 Boys and girls (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years) who are long-term ALL survivors (41.5 years posttreatment) have significantly reduced cardiorespiratory fitness, and this reduction is correlated with cumulative chemotherapy dose. 7 Likewise, higher chemotherapy dose is associated with lower cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,11,17,18 In the mean time, greater efforts should be made to establish reference values for these functional tests predicated on specific cancer diagnoses. 6,18 The emerging picture of the functional capacity of SCT recipients is one of significant decline during and immediately after transplantation 2,19,20 followed by limited or no improvement of functional capacity during the sub-acute phase of recovery. [19][20][21] Results from this study provide further support of this clinical picture.…”
Section: Groupmentioning
confidence: 99%
“…However, available data suggest that pre-transplantation chemotherapy and the transplant process leave many of these patients with substantial physical and functional deficits. [1][2][3] As such, physical rehabilitation of these patients becomes an important post-transplant therapeutic intervention which is often directed by rehabilitation specialists, including occupational and physical therapists. 4,5 Central to the success of this rehabilitation process is an understanding of the initial physical and functional status of the patient and an ability to monitor changes in patient status over the course of rehabilitation treatment.…”
Section: Introductionmentioning
confidence: 99%